1997
DOI: 10.1095/biolreprod56.1.59
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Natriuretic Peptide and the Guanylyl Cyclase Receptors in the Rat Ovary are Modulated by the Estrous Cycle1

Abstract: We have previously shown that rat ovaries synthesize atrial natriuretic peptide (ANP) and express the cognate guanylyl cyclase (GC-A and GC-B) receptors for ANP. Since another natriuretic peptide, termed the C-type natriuretic peptide (CNP), can also interact with these receptors, we have investigated whether rat ovaries express CNP and if so, whether the concentration of this natriuretic peptide and the guanylyl-cyclase receptors are influenced by the estrous cycle. CNP mRNA was detected in rat ovaries using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…CNP originally isolated from porcine brain (26) and shown as a neurotransmitter is now considered an important component of peripheral tissues including vascular endothelium (29) and ovaries (30). The actions of CNP are different from those described for ANP and BNP.…”
Section: Natriuretic Peptide Familymentioning
confidence: 99%
“…CNP originally isolated from porcine brain (26) and shown as a neurotransmitter is now considered an important component of peripheral tissues including vascular endothelium (29) and ovaries (30). The actions of CNP are different from those described for ANP and BNP.…”
Section: Natriuretic Peptide Familymentioning
confidence: 99%
“…As well as the profound effects on endochondral ossification, these models of disrupted CNP/GC-B pathways suggest potentially important roles of this system in pituitary and gonadal tissues as Npr2 K/K mice are GH deficient and exhibit female infertility (Tamura et al 2004). Further support for CNP as a regulator of reproductive function comes from several studies that have shown CNP to potently stimulate cGMP production in GNRH neurons (Olcese et al 1994), pituitary gonadotrophs (McArdle et al 1993), and endocrine cells of the testis, ovaries, placenta and uterus (Khurana & Pandey 1993, Huang et al 1996, Middendorff et al 1996, Acuff et al 1997, Jankowski et al 1997, Gutkowska et al 1999, Stepan et al 2001, Walther & Stepan 2004, implicating CNP function at all levels of the hypothalamo-pituitarygonadal (HPG) axis. Furthermore, cGMP is a useful pharmacological target in the treatment of male reproductive disorders (Rosen & McKenna 2002, Christ & Hodges 2006.…”
Section: Introductionmentioning
confidence: 98%
“…LH signaling is known to decrease the amount of CNP in rat and mouse ovaries (Jankowski et al, 1997;Kawamura et al, 2011;Liu et al, 2014) and in human and porcine follicular fluid (Kawamura et al, 2011;Zhang et al, 2014); the decrease in the levels of CNP is associated with a decrease in Nppc mRNA (Kawamura et al, 2011;Tsuji et al, 2012;Liu et al, 2014). However, in the mouse ovary, where the kinetics are best characterized, the CNP decrease is first detected at 2 h Liu et al, 2014), whereas the decrease in cGMP is detected at 15 to 20 min (Norris et al, 2010;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%